Seismic Performance Assessment of Sustainable Shelter Building Using Microtremor Method - Putra, Rusnardi Rahmat; Kiyono, Junji; Ono, Yusuke; Saputra, Dezy (Salehan Institute of Higher Education, 2024)
The increasing intensity of earthquakes in West Sumatra could trigger megathrust earthquakes and tsunamis at the inter-plate in the Mentawai Islands. Building assessments are necessary to determine their vulnerability to predicted earthquakes. The target is a four-story building that serves as an education building and vertical evacuation. This research proposes a complete vulnerability assessment method using single microtremor observations, and the results are used to determine seismic building performance. The natural frequency is derived from the spectral analysis of the horizontal components (NS and EW) for each level, and we considered the largest earthquake peak ground motion (PGA) in this region to be the September 30, 2009, Padang earthquake (PGA 380 gals as ground motion input). We calculated the resonance index, seismic vulnerability index, and damping ratio. The results show that the resonance index of the structure is less than 1, the vulnerability index of the UNP Faculty of Economics building ɤ > (1/100-1/200) and is 1/234 to 1/699 for the x direction and 1/207 to 1/709 for the y direction; the average damping ratio is <5% for both directions (x, y) and RDM and FSR relationship is 0.78 and 0.69 for x and y respectively. The overall findings indicate that the structural response of the evaluated buildings falls within the 'slight' damage category during seismic events. Doi: 10.28991/CEJ-2024-010-11-06 Full Text: PDF